1984
DOI: 10.1002/j.1552-4604.1984.tb01826.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Hemodynamic Effects of Tiapamil: Exercise Performance, Thallium Stress Scintigraphy, and Radionuclide Ventriculography

Abstract: The pharmacokinetic behavior and hemodynamic effects of tiapamil, a calcium antagonist, were studied in 16 cardiac patients during an eight-day treatment course, giving oral doses of 600 mg daily. The hemodynamic effects were investigated using exercise performance tests, thallium stress scintigraphy, and radionuclide ventriculography. The areas under the plasma concentration-time curve after the final dose were greater than after the first dose for both tiapamil (+53 per cent) and its metabolite (+24 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There was no exacerbation of LV dysfunction in five patients with marked impairment of LV performance (EF < 40%) (4). In another study, oral tiapamil (400-600 mg) produced a significant improvement in LVEF (+ 18%) and cardiac output (+ 12%) (12). In patients with ischemic heart disease undergoing cardiac catheterization, intravenous tiapamil produced a fall in TPR, without affecting the heart rate or dLVP/dt,,,, but increasing cardiac output (3,45).…”
Section: Antianginal Effectsmentioning
confidence: 87%
See 1 more Smart Citation
“…There was no exacerbation of LV dysfunction in five patients with marked impairment of LV performance (EF < 40%) (4). In another study, oral tiapamil (400-600 mg) produced a significant improvement in LVEF (+ 18%) and cardiac output (+ 12%) (12). In patients with ischemic heart disease undergoing cardiac catheterization, intravenous tiapamil produced a fall in TPR, without affecting the heart rate or dLVP/dt,,,, but increasing cardiac output (3,45).…”
Section: Antianginal Effectsmentioning
confidence: 87%
“…In patients with liver cirrhosis, the volume of distribution has been shown to increase, leading to a prolonged half-life of tiapamil (28). Following repeated oral administration of tiapamil to patients with ischemic heart disease, there was a significant increase in the area under the plasma concentration-time curve of tiapamil(+53%) and its N-desmethyl metabolite (+24%) when measured following the last dose (12). It has been suggested that, in addition to hepatic biotransformation, tiapamil may undergo saturable intestinal wall metabolism (1237).…”
Section: Pharmacokineticsmentioning
confidence: 99%